The Platonia insignis Mart. as the Promising Brazilian ‘Amazon Gold’: The State-of-the-Art and Prospects - Simone Kelly Rodrigues Lima; Angélica Gomes Coêlho; Massimo Lucarini; Alessandra Durazzo; Daniel Dias Rufino Arcanjo (Agriculture, 2022)
Bacuri (Platonia insignis) is a monotype belonging to the Clusiaceae family. Of Amazonian origin, it is highly appreciated for fresh consumption, mainly due to its peculiar sensory characteristics. It is also widely used in the food industry, mainly in pulp (endocarp), used in the manufacture of beverages, jellies, and ice cream. Although the use of pulp is well established in the food sector, recently, research has turned attention to the use of other parts of the fruit and plant, especially in the therapeutics, cosmetics, and fuel sectors. Its bioactive components have been investigated for having important antioxidant, anti-inflammatory, immunomodulatory, hypotensive, cardioprotective, antiepileptic, antileishmanial, and antifungal activities, among others, mainly attributed to the presence of compounds such as xanthones, terpenes, phenolics, and fatty acids. Thus, this study aimed to gather data on the species Platonia insignis Mart. through an integrative review of the agronomic, nutritional, physical–chemical characteristics and a technological prospection about its applications. The study showed that in the last ten years there has been a significant increase in the number of patents deposited, with the prospect that with the advancement of studies on their properties, results for application in the most diverse areas will prove increasingly viable and promising.